2014
DOI: 10.1186/1478-7547-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost-effectiveness of nutrition supplementation for malnourished, HIV-infected adults starting antiretroviral therapy in a resource-constrained setting

Abstract: BackgroundLow body mass index (BMI) individuals starting antiretroviral therapy (ART) for HIV infection in sub-Saharan Africa have high rates of death and loss to follow-up in the first 6 months of treatment. Nutritional supplementation may improve health outcomes in this population, but the anticipated benefit of any intervention should be commensurate with the cost given resource limitations and the need to expand access to ART in the region.MethodsWe used Markov models incorporating historical data and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…While nutritional supplementation and food assistance have effectively increased BMI in some [5457], but not all studies [58], such interventions have not been shown to significantly decrease short-term mortality risk in HIV-infected adults [58, 59]. However, evidence is limited and nutritional supplementation has been shown to be cost-effective for reducing mortality in severely underweight individuals [60].…”
Section: Discussionmentioning
confidence: 99%
“…While nutritional supplementation and food assistance have effectively increased BMI in some [5457], but not all studies [58], such interventions have not been shown to significantly decrease short-term mortality risk in HIV-infected adults [58, 59]. However, evidence is limited and nutritional supplementation has been shown to be cost-effective for reducing mortality in severely underweight individuals [60].…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Food and nutrition therapy administration (FNTA) is important and integral in the management of HIV/AIDS patients in both self and managed care [10,11], especially in Developing Countries where weight loss is widespread due to malnutrition [12]. According to Koethe et al [13] and Martinez et al [14], in Sub-Saharan Africa and Honduras, there are high death rates and low health outcomes in HIV/AIDS patients who start anti-retroviral therapy (ART) with low body mass index (BMI), which mandates FNTA under severe personal and organisational resource limitations. Further to this, Cark and Cress [15] point out that FNTA should be personalised in order to be effective for HIV/AIDS patients, which requires any appropriate technologies to support customisation of incorporated knowledge.…”
Section: The Challenge Of Supporting Food and Nutrition Therapy Fmentioning
confidence: 99%
“…In the areas of food insecurity, this action is quite limited. Besides the food shortage in these regions, ensuring adequate food supply requires government strategic planning to better access to health networks and nutritionists, that is, it involves costs often unavailable in nutritional risk areas [31,66].…”
Section: Multivitaminsmentioning
confidence: 99%